D'yakonov–Perel and Elliot–Yafet spin relaxation rates in InGaAs/InAlAs multiple quantum wells at room temperature. (1st April 2022) - Arikawa, Ayuki; Saito, Yasuhito; Nakanishi, Koichi; Sato, Shota; Sugaya, Kyohei; Yokota, Nobuhide; Kohda, Makoto; Morita, Ken
Abstract: Room-temperature spin relaxation rates resulting from the D'yakonov–Perel (DP) and Elliot–Yafet (EY) mechanisms were determined by combining microscopic and macroscopic Kerr rotation measurements in narrow-gap (001) InGaAs/InAlAs quantum wells (QWs). Two samples with different DP relaxation rate were compared and we found that EY relaxation rate ( 3.80 GHz ) was approximately double the value of the average DP relaxation rate even in the asymmetric QWs with large spin–orbit parameters. We also found that the anisotropy of spin relaxation time owing to the DP mechanism is weakened significantly in the system in which the EY mechanism dominates the spin relaxation.